Adaptive Leadership in Managing Conflict to Improve Performance - Popi Hidayanti; Helmawati (CV. Media Digital Publikasi Indonesia, 2025)
Schools are complex organizations where conflicts may arise from both technical issues and interpersonal relations. This study investigates conflicts at SDN Bojongmekar, particularly between senior and junior teachers and those related to limited resources. It also explores the adaptive leadership strategies of the principal, the supporting and inhibiting factors, and the impact on teacher performance. Using a qualitative case study approach, data were collected through interviews, observations, and document analysis, and analyzed thematically with source triangulation to ensure validity. The findings indicate that conflicts mainly occur as internal organizational and interpersonal tensions between senior and junior teachers. The principal applied adaptive leadership through structured steps, supported by open communication, while seniority culture remained the main barrier. Adaptive leadership was found to improve teacher motivation, collaboration, and the overall work climate. In conclusion, adaptive leadership transformed conflict into opportunities to enhance teacher performance and build a more conducive environment for quality learning.